2016
DOI: 10.1021/acsami.6b05471
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Tracking of the Osteogenic Differentiation of Mouse BMSCs by Aggregation-Induced Emission Nanoparticles

Abstract: Bone marrow-derived mesenchymal stem cells (BMSCs) have shown great potential for bone repair due to their strong proliferation ability and osteogenic capacity. To evaluate and improve the stem cell-based therapy, long-term tracking of stem cell differentiation into bone-forming osteoblasts is required. However, conventional fluorescent trackers such as fluorescent proteins, quantum dots, and fluorophores with aggregation-caused quenching (ACQ) characteristics have intrinsic limitations of possible interferenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 40 publications
0
30
0
Order By: Relevance
“…BMSCs are capable of osteogenic differentiation, which indicates the prospect of the clinical application for biotherapy based on BMSCs (19). Osteogenic differentiation of BMSCs, in vitro and in vivo, has been extensively studied (20,21). The results of the present study demonstrated that glycitin promotes cell proliferation, osteoblast induction, and activates Col I mRNA expression and ALP activity of BMSCs.…”
Section: Discussionmentioning
confidence: 51%
“…BMSCs are capable of osteogenic differentiation, which indicates the prospect of the clinical application for biotherapy based on BMSCs (19). Osteogenic differentiation of BMSCs, in vitro and in vivo, has been extensively studied (20,21). The results of the present study demonstrated that glycitin promotes cell proliferation, osteoblast induction, and activates Col I mRNA expression and ALP activity of BMSCs.…”
Section: Discussionmentioning
confidence: 51%
“…A similar magnitude of large Stokes shift (160 to 180 nm) has not only been observed in dyes but also in dyes that aggregate to form nanoparticles. 37,38 If we look carefully at the excitation spectrum ( Fig. 4c) instead of the absorption spectrum (the former being more sensitive than the latter), we will notice that the tail of the excitation spectrum is extended to 550 nm.…”
Section: Resultsmentioning
confidence: 99%
“…Given that ideal fluorescent agents for fluorescence imaging should possess large Stokes shift, excellent photostability, highly efficient emission, and free of ACQ effect, AIEgens are good candidates. In fact, AIEgens have been widely applied for monitoring biological processes,19c such as osteogenic differentiation, droplet‐lysosome interplay, autophagy, mitophagy, apoptosis, cancer cell progression, tumor growth,49b,61 macrophage phagocytosis, embryonic development, and lipid metabolism . Herein, we discuss some other recent examples that were performed in small animal models.…”
Section: Monitoring Biological Processesmentioning
confidence: 99%
“…As discussed, AIEgens outperform conventional contrast agents (e.g., quantum dots, rare‐earth‐doped NPs, and semiconductor polymer dots), in terms of their superior photobleaching‐resistance, low toxicity, high fluorescent efficiency, and lack of ACQ effect. Indeed, stem cell tracking based on AIEgens has attracted increasing attention in recent years . For example, Yang et al71c used NIR fluorescent AIE dots (TP‐TPACN dots) for in vivo tracking of transplanted adipose‐derived stem cells (ADSCs), and visualized the therapeutic mechanism of ADSCs in an X‐ray radiation‐induced skin injury mouse model ( Figure A,B).…”
Section: Monitoring Biological Processesmentioning
confidence: 99%